Local Wisdom as a Strategic Capital in Educational Management and Learning Transformation - Nurdiana, Nurdiana; Sutarto, Joko; Wasino, Wasino; Raharjo, Tri Joko; Taufikin, Taufikin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze how educational management develops a local wisdom-based curriculum as a strategy to improve learning quality. This study employs a multi-case qualitative design conducted in three public high schools in Aceh: SMA 1 banda Aceh, SMA 3 Banda Aceh, and SMA 1 Pidie. Data were collected from 20 participants, including school principals, teachers, students, and customary leaders, through semi-structured in-depth interviews, non-participant classroom observations, and analysis of curriculum-related documents such as syllabi, lesson plans, and school program records. Data were analyzed thematically using a systematic coding process involving open, axial, and selective coding to identify patterns across cases and construct conceptual categories. Findings show that local wisdom functions as strategic curriculum capital, strengthening institutional legitimacy, increasing student engagement in learning, and fostering a more solid moral and social identity. The integration of values such as hospitality ethics, collective solidarity, and customary norms not only enriches teaching materials but also builds collaborative governance between schools and communities. The professional transformation of teachers occurs through a shift in their role from material deliverers to designers of culturally based, contextually relevant curricula. This model results in increased learning relevance, active student participation, and community trust in schools. This study formulates a Strategic Cultural Curriculum Management model that positions local wisdom as a form of educational managerial capital. Its contribution broadens the discourse on curriculum management, educational governance, and learning quality in the global context.